Are serum levels of ADAMTS5, TAS and TOS at 24–28 gestational weeks associated with adverse perinatal outcomes in gestational diabetic women?. (3rd July 2020) - Ozler, Sibel; Oztas, Efser; Gumus Guler, Basak; Erel, Ozcan; Turhan Caglar, Ali; Ergin, Merve; Uygur, Dilek; Danisman, Nuri
Abstract: We aimed to determine the role of placental A Disintegrin and Metalloproteinase with thrombospondin motifs 5 (ADAMTS5), and maternal serum ADAMTS5, total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI) levels at 24–28th gestational weeks in GDM. This study included 57 patients, who had been diagnosed as having GDM at their 24–28th gestational week, and 29 controls. The maternal blood samples were collected at the 24-28th gestational week and ADAMTS5 was studied with the enzyme-linked immunosorbent assay (ELISA) method, whereas an automated colorimetric method was used to study TAS, TOS, and OSI. The level of ADAMTS5 in maternal serum of patients with GDM were significantly lower than the controls ( p =  .017); whereas TOS and OSI levels were significantly higher (p = . 003 and p = . 008). Multivariable logistic regression analysis revealed ADAMTS5 and TOS levels were independently associated with adverse perinatal outcomes ( p = . 004 and p = . 018). We found that serum ADAMTS5 levels decreased and TOS level increased in GDM pregnant at 24–28th gestational weeks. In addition, we found that increased levels of serum ADAMTS5 and decreased TOS levels at 24–28th weeks were associated with adverse perinatal outcomes independent of the mode of treatment in GDM. Impact statement: What is already known on this subject? Gestational diabetes mellitus (GDM) is one of the most common medical complications of pregnancy. The insulin resistance, which starts at the 24–28th gestational weeks, increases during gestation. GDM increases maternal complications like preeclampsia, cesarean rate, cardiovascular disease, obesity, and diabetes after pregnancy; and neonatal complications like macrosomia, hypoglycemia, hyperbilirubinemia, delivery trauma, shoulder dystocia, and adult-onset obesity, and diabetes. What the results of this study add? A significant relationship between ADAMTS5, TOS levels and adverse perinatal outcome. insulin resistance and was observed. What the implications are of these findings for clinical practice and/or further research? Based on this finding, we concluded that increased levels of oxidative stress and decreased ADAMTS5 levels are associated with GDM and predictive for adverse perinatal outcomes. The results of the present study were consistent with the previous reports and indicated that increased oxidative stress in GDM patients are related to adverse perinatal outcomes.